2015
DOI: 10.1016/j.humimm.2015.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Common variants of chemokine receptor gene CXCR3 and its ligands CXCL10 and CXCL11 associated with vascular permeability of dengue infection in peninsular Malaysia

Abstract: Dengue causes significantly more human disease than any other arboviruses. It causes a spectrum of illness, ranging from mild self-limited fever, to severe and fatal dengue hemorrhagic fever, as evidenced by vascular leakage and multifactorial hemostatic abnormalities. There is no specific treatment available till date. Evidence shows that chemokines CXCL10, CXCL11 and their receptor CXCR3 are involved in severity of dengue, but their genetic association with the susceptibility of vascular leakage during dengu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The chemokines CXCL10, CXCL11 and its respective chemokine receptor CXCR3 were reported as biomarkers for severe form of dengue infection [ 57 ]. These results are in agreement with recent emerging data indicating strong association between CXCL10, CXCL11 and CXCR3 and vascular permeability [ 58 ]. The three genes are components of the NF-kB pathway and are involved in the pathogenesis of SARS and West Nile virus encephalitis [ 59 , 60 ].…”
Section: Introductionsupporting
confidence: 94%
“…The chemokines CXCL10, CXCL11 and its respective chemokine receptor CXCR3 were reported as biomarkers for severe form of dengue infection [ 57 ]. These results are in agreement with recent emerging data indicating strong association between CXCL10, CXCL11 and CXCR3 and vascular permeability [ 58 ]. The three genes are components of the NF-kB pathway and are involved in the pathogenesis of SARS and West Nile virus encephalitis [ 59 , 60 ].…”
Section: Introductionsupporting
confidence: 94%
“…In DHF and DSS, the association between paracellular endothelial hyperpermeability and plasma leakage had been extensively investigated 8 9 10 11 . However, whether transcellular endothelial leakage exists and is involved in DHF and DSS remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cell has an ability to regulate its paracellular (through intercellular junctions) and transcellular (through endothelial cell) transports of fluid, solutes, and proteins 6 7 . The association between paracellular endothelial hyperpermeability and plasma leakage has been extensively investigated in several diseases, including DENV infection 8 9 10 11 . Previous studies have postulated that immunological host response can enhance the disruption of endothelial intercellular junctions, resulting in paracellular leakage of plasma from intravascular space to serous cavities 8 9 10 11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mezger et al reported an association between the recipient CXCL10 and the development of invasive aspergillosis in a European cohort of 81 allo-HSCT recipients (Mezger et al, 2008 ). The variant 642C/G, which is determined by the rs3921 SNP, has been associated with susceptibility to other infections (Pineda-Tenor et al, 2014 ; Hoh et al, 2015 ). In a larger cohort of 652 HSCT Japanese patients who underwent unrelated HLA-matched (BMT) for hematologic malignancies, our group found that a recipient C/G or G/G genotype associated with a significantly better 5-year overall survival (OS) rate, a lower TRM rate and a reduced incidence of death due to organ failure compared with the recipient C/C genotype (Nakata et al, 2013 ).…”
Section: Non-hla Variants and Infectious Complications After Hsctmentioning
confidence: 99%